PERSENGKETAAN PERDAGANGAN ANTARA INDONESIA DAN AMERIKA SERIKAT DALAM EKSPOR UDANG KE AMERIKA SERIKAT TAHUN 2010-2013 - Rahman, M Kharif; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
States of America. Indonesia is the country's largest shrimp exporter to theUnited States. The dispute began on charges filed by the Coalition of Gulf ShrimpIndustries (COGSI) to the Indonesian government because they feel there has beenan unfair trade related influx of U.S. shrimp imports cheaper than U.S domesticshrimp. The Indonesian government has been accused of giving subsidies toexporters to suppress the price of shrimp is marketed to the U.S. Disputes that havehappened to be disrupted for trade between the two countries, especially shrimpexports to the United States.This study used a theory of justice by Adam Smith. This theory is intended toprotect from the loss ("the end of justice is to secure from injure") caused by unfairtrade in international trade. In addition, the U.S. and Indonesia feel there has beenan unfair trade, so that the application of fair trade should be applied in order toavoid trade disputes. The scope of this study is from 2010-2013.Keywords: Disputes, Unfair Trade, Export, Import, COGSI, and Shrimp